Development of Tourism Activities Based on Sustainable Livelihood Approach in Huta Tinggi Tourism Village - Sitorus, Nova Bernedeta; Liyushiana; Sianipar, Christina Indriany (Politeknik Pariwisata Lombok, 2025)
Introduction: This study aims to determine the development of tourism activities in Huta Tinggi Tourism Village with the Sustainable Livelihood Approach. Here are the two research questions used: (1) How can the Sustainable Livelihood Approach (SLA) be effectively implemented to optimize the development of tourism activities in Huta Tinggi Tourism Village? (2) What are the key challenges and opportunities in fostering community involvement and empowerment for sustainable tourism development in Huta Tinggi Tourism Village? Methodology: This study uses a qualitative research approach with narrative/descriptive research methods. The key informants in this study were the Head of Pangururan Sub-District, the Manager of the Huta Tinggi Tourism Village, and the local community. Findings: This study found that Huta Tinggi Tourism Village has significant potential for the development of culture- and nature-based tourism, offering attractions such as traditional cooking, Batak Toba cultural art classes, and activities like buffalo milking and coffee harvesting. However, community participation in tourism management remains low, highlighting the need for human resource empowerment through training, facility improvements, and raising awareness of the importance of tourism. Conclusion: Huta Tinggi Tourism Village offers unique cultural attractions and local wisdom that appeal to both domestic and international tourists. To maximize the potential of this village, stages of human resource development, including awareness, skill transformation, and intellectual enhancement, are essential. Ensuring adequate facilities, financial management training, community involvement, and continuous monitoring will further enhance the quality of tourist experiences and support sustainable development in Huta Tinggi.